Population and Production of Seed of Buchanania lanzan Spreng in Dhenkanal Forest Division of Odisha, India - Chandra, Girish; Tamta, B. P.; Mohanty, M.; Pandey, Abhay Pratap; Latpate, Raosaheb (Indian Forester, 2023)
Buchanania lanzan is a deciduous tree belonging to the family Anacardiaceae. Tasty ripen fruit (berry) is nutritive, and the kernel (after decortications of the hard shell of the seed/ stone) is known as Chironji for trade. Chironji not only gives attractive prices to primary collectors but also generates employment for the rural workforce during the lean period. In the present study, the method of Stratified Ranked Set Sampling and Adaptive Cluster Sampling has been used in Dhenkanal Forest Division, Odisha, India. There are about 43,96,000 poles and trees in the division with a seed yield of 821.4g/tree/year and 72% eligible fruit bearer leading to 1,200t seed/year. The highest number of seedlings and saplings along with maximum yield was found in the Hindol range, however, the mean Chironji yield per tree in terms of fresh berry weight (7.02kgÂ±1.10) and dry seed weight (1.67Â±0.26) are found highest in Sadangi which significantly differs with other forest ranges. This shows that yield per tree is not the same across all areas under study. Tree girth is positively and negatively correlated to the seed yield and hundred seed weight respectively. If the biotic/abiotic factors operate within the threshold limit, productivity can be assured sustainably.